Human Capital Flight : Impact of Migrationon Income and Growth. (IMF Working Papers; Working Paper, 1994)
This paper analyses the impact of government tax and subsidy policy on immigration of human capital and the effect of such immigration on growth and incomes. In the context of a two-country endogenous growth model with heterogeneous agents and human capital accumulation, we argue that human capital flight or 'brain drain' arising out of wage differentials, say because of differences in income tax rates or technology, can bring about a reduction in the steady state growth rate of the country of emigration. Additionally, permanent difference in the growth rates as well as incomes between the two countries can occur making convergence unlikely. While in a closed economy, tax-financed increases in subsidy to education can have a positive effect on growth, such a policy can have a negative effect on growth when human capital flight is taking place. Since subsidizing higher education is more likely to induce substantial brain drain, it is likely to be inferior to subsidy to lower levels of education if growth is to be increased.